The Influence of Motivation, Self-Potential, and Socio-Economic Conditions on The Interest in Continuing to Higher Education - Wahyu Widodo; Tohir Tohir; Cut Misni Mulasiwi (Economic Education Analysis Journal, 2023)
This study aimed to analyse the influence of motivation, self-potential, and socio-economic condition of parents on the interest in continuing to higher education for class XI students for the 2022/ 2023 academic year at Public High School 1 Baturraden. This research is quantitative research using survey method. The population in this study were 358 students using probability sampling technique using simple random sampling using the Slovin formula which resulted in 189 samples. The method in collecting research data used questionnaires, and the data processing method used multiple linear regression analysis. The results of the study show that: motivation has a positive influence on the interest in continuing to higher education; Self-potential has a positive influence on interest in continuing to higher education; and Socio-economic conditions of parents have a positive influence on the interest in continuing to higher education.